Hiding in plain sight: Reinvasion risk from retained seed after dispersal events in introduced conifers - Thomas F. Carlin; Tyler P. Roberts; Matthew B. Scott; Ryan S. Vorster; Carol A. Rolando; Thomas S H Paul (Trees, Forests and People)
Non-native conifers are the most successful tree-weeds in the Southern Hemisphere, reproducing annually through seed-bearing cones. Rather than shedding cones, some conifer species retain cones on the tree indefinitely (e.g. Pinus contorta), meaning cones persist on the tree even after mortality via common foliar applied herbicide-based control methods. We investigated whether open cones could present a reinvasion risk by retaining seeds after their primary dispersal event and disseminating them over time. We found that 19 % of open cones retained viable seed after opening, with an average of 3.5 viable seeds (ranging from 1-39) per cone. The oldest cone retaining viable seed was 15 years old. The majority of seeds had separated from their wing 6 years after the initial cone opening, however intact wings were recovered up to 11 years post cone opening. These results suggest that cones can still contribute to propagule pressure even after their main dispersal event, potentially leading to the reinvasion of sites years after control operations. However, as the majority of seeds detach from their wings only a few years after cone opening their dispersal ability is hampered and reinvasion would likely occur close to the parent tree.